Development of a Football Game Modification Book for Primary School Physical Education and Health Teachers (Department of Physical Education, Sport, Health and Recreation, 2020)
The purpose of this study was to determine whether the development of a football game modification book can be used as an alternative reference media for learning football games. The product development of this football game modification book was evaluated by experts in football game materials and learning media experts. This research was conducted using research and development, which is used to produce certain products. The sample were all sports and health education teachers in Tugu District totaling 28 teachers. The research instrument used a semi-open questionnaire and data analysis used descriptive statistics. The results of data analysis from 28 teacher respondents got a score of 88%, it can be concluded that the development of a football game modification book is in a good category and can be used as an alternative reference media in learning football games for sports and health physical education teachers.